PROGRAM KELUARGA LANSIA SEHAT FISIK-MENTAL DAN BERDAYA (KLASIKAL-YA) DALAM PENGELOLAAN SAMPAH ORGANIK RUMAH TANGGA DI POSYANDU LANSIA ASTER, BANTUL: - Wantonoro; Salmiyati, Suri; Sugiantoro, Hari Akbar (Jurnal Abdi Insani, 2024)
The Family Program for Healthy Physically-Mentally and Empowered Elderly (Klasikal-ya) in the management of household organic waste at the Aster Elderly Posyandu, Bantul, Yogyakarta is a Community Service activity aimed at maintaining and improving the physical and mental health of the elderly with physical and social activities in the form of managing household organic/kitchen waste using a composter for leftover kitchen waste (LOSIDA) which produces compost which is then used to grow productive home garden plants, of course adjusted to the functional capacity of the elderly participants. This program is integrated with TiM at the University (Universitas 'Aisyiyah Yogyakarta) which targets the elderly as the main focus by involving the active role of competent students and educators (lecturers). The implementation of activities begins with socialization to introduce the program for healthy physically and mentally and productive elderly; Training, carried out with counseling on healthy activities for the elderly in managing household organic waste using the LOSIDA method. Application of Technology with screening and activities to improve physical and mental health, making and implementing the LOSIDA composter; Mentoring and Evaluation; Monitoring the physical and mental health of the elderly, and utilizing compost from activities for home planting activities as a healthy physical and mental activity for the elderly. Sustainability of the Program; carried out with periodic communication/consultation channels. The benefits of this program are specifically to increase the physical activity of the elderly according to their functional capacity which will have a positive effect on the mental health of the elderly. Increasing community participation, especially the elderly, in dealing with organic waste which can then be used productively through useful home yard plants